Prospects Pertaining to Application of Heat-and-Pump Technology in Power-and-Hear generation Complex - A. V. Ovsiannik; O. L. Rykhter; I. I. Matsko; S. O. Bobovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The existing conditions of heat supply operation create favorable possibilities for repeat involvement of large capabilities of low-potential heat at power objects of heat supply system in the fuel and energy balance of urban power engineering facilities and, first of all, it is possible due to introduction of power-saving heat-and-pump technology.Diversity of conditions concerning organization of heat supply and sources of low-potential heat which can be used with the help of heat-and-pump technology in the system of centralized heat-supply reveals the necessity to take more serious approach to investigation of real possibilities of their application, owing to them it is possible to involve repeatedly used heat in the technological cycle of the urban power-and-heat generation complex.